(untitled) (Conferencea, 2024)
Olympic fire Olympic games traditional attribute which antique since ancient times takes the beginning . Olympic of fire of the sun with rays ( special lenses through ) lighters idea belongs Pierre De Coubertin . this idea He in 1912 put up .